Negative pole piece of lithium ion battery, preparation method of negative pole piece and lithium ion battery
By adopting a double-layer structure design of graphite layer and hard carbon layer in the negative electrode sheet of lithium-ion battery, the problems of polarization and energy density reduction in lithium-ion battery during fast charging are solved, and high-rate charging and high energy density are achieved, and the flexibility of the electrode sheet is improved.
Patent Information
- Application Number
- CN202411905597.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-01
AI Technical Summary
Lithium-ion batteries are prone to polarization during fast charging, resulting in an increase in DC internal resistance, affecting energy density and fast charging performance. At the same time, extreme sheets with high surface density and compaction density are prone to breaking and powder loss.
The negative electrode sheet design adopts a double-layer structure, including a graphite layer and a hard carbon layer. The graphite layer is arranged on both sides of the negative current collector, and the hard carbon layer is arranged on the side of the graphite layer away from the negative current collector. Through the appropriate surface density, compaction density and particle size design, a specific relationship is met to improve the fast charging performance and energy density of the battery.
It realizes fast lithium ion conduction during high-rate charging of lithium-ion batteries, avoids lithium-ion evolution, improves the fast charging performance of the battery, maintains a high energy density, and improves the flexibility of the electrode sheet, reducing the breakage and powder loss problems during processing.
Smart Images

Figure CN119742316A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion battery electrode materials, and in particular to a lithium ion battery negative electrode sheet and a preparation method thereof, and a lithium ion battery. Background Art
[0002] The information disclosed in the background of the invention is only intended to enhance the understanding of the overall background of the invention and should not be necessarily regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] At present, new energy vehicles occupy an increasing share in the market, but the charging speed has always been a problem that consumers pay great attention to. The improvement of fast charging technology for lithium-ion batteries is imminent. Improving its fast charging performance while maintaining a high energy density is one of the key tasks in the industry.
[0004] The fast charging performance of a battery is often related to the polarization inside the battery. One of the direct manifestations is the size of the battery's DC internal resistance (DCR), and the surface density and compaction density of the negative electrode are the key factors affecting DCR. High surface density and compaction density can increase the volume energy density of the battery, but will reduce the porosity of the active coating, thereby affecting the conduction of lithium ions and reducing the fast charging performance; at the same time, high surface density and compaction density will cause the electrode to become brittle and hard, and it is easy to break and lose powder during processing. However, if a low surface density and compaction density are selected, although the porosity of the electrode increases, the conductive network in the coating is difficult to form, which will also result in large impedance and accelerated polarization, which is not conducive to the long-term use of the battery; and it will lead to a decrease in the battery's energy density. In view of this, it is indeed necessary to provide a negative electrode sheet with a suitable negative electrode surface density and compaction density to improve the flexibility of the electrode sheet, so that the battery has good fast charging performance while ensuring that the energy density is not lost. Summary of the invention
[0005] In view of this, the present invention provides a lithium ion battery negative electrode plate and a preparation method thereof, and a lithium ion battery. The lithium ion battery negative electrode plate of the present invention can maintain a high energy density while achieving high rate charging, and has low material cost and good application prospects.
[0006] In a first aspect, the present invention provides a negative electrode plate for a lithium-ion battery, comprising:
[0007] Anode current collector;
[0008] A graphite layer is disposed on both sides of the negative electrode current collector; the graphite layer comprises graphite particles, a conductive agent and a binder;
[0009] A hard carbon layer is arranged on the surface of the graphite layer away from the negative electrode current collector; the hard carbon layer comprises hard carbon particles, a conductive agent and a binder;
[0010] Wherein, the graphite layer and the hard carbon layer satisfy the relationship shown in Formula I:
[0011] 1.4≤ρ1*D1+ρ2*D2+PD≤1.75 Formula I;
[0012] Where ρ1 is the surface density of the hard carbon layer in g / cm 2 D1 is the D50 value of the hard carbon particles in the hard carbon layer when the unit is μm; ρ2 is the surface density of the graphite layer in g / cm 2 D2 is the surface density value of the graphite layer when D50 is in μm; PD is the compacted density in g / cm 3 The overall compacted density value at .
[0013] Preferably, the mass ratio of the graphite layer to the hard carbon layer is (40:60) to (60:40).
[0014] Preferably, the graphite layer and the hard carbon layer satisfy the relationship shown in Formula II:
[0015] 1.5≤ρ1*D1+ρ2*D2+PD≤1.72Formula II.
[0016] Preferably, ρ1 is 0.0048-0.012; D1 is 3-18; ρ2 is 0.0048-0.012; D2 is 8-20; and PD is 1.3-1.6.
[0017] Furthermore, ρ1 is 0.006-0.01; D1 is 5-10; ρ2 is 0.006-0.01; D2 is 10-18; and PD is 1.35-1.55.
[0018] Preferably, in the graphite layer, the mass ratio of graphite particles, conductive agent and binder is (90-95):(2-5):(2-5).
[0019] Preferably, in the hard carbon layer, the mass ratio of the hard carbon particles, the conductive agent and the binder is (90-95):(2-5):(2-5).
[0020] Preferably, the total mass per unit area of the graphite layer and the hard carbon layer on one side of the negative electrode current collector is 6 to 10 mg / cm 2 .
[0021] In a second aspect, the present invention provides a method for preparing the above-mentioned negative electrode sheet of a lithium ion battery, comprising the following steps:
[0022] Graphite particles, conductive agent and binder are mixed evenly with solvent to form a first slurry, hard carbon particles, conductive agent and binder are mixed evenly with solvent to form a second slurry, and the first slurry and the second slurry are coated on one side of the negative electrode collector by double-layer coating equipment, and the first slurry is in contact with the surface of the negative electrode collector; after drying, the first slurry and the second slurry are coated on the other side of the negative electrode collector in the same way, and the first slurry is in contact with the surface of the negative electrode collector, and the negative electrode sheet of the lithium-ion battery is obtained after drying.
[0023] In a third aspect, the present invention provides a lithium-ion battery, comprising a positive electrode plate, a negative electrode plate, a separator and an electrolyte, wherein the negative electrode plate is the above-mentioned lithium-ion battery negative electrode plate or the lithium-ion battery negative electrode plate prepared by the above-mentioned preparation method.
[0024] Compared with the prior art, the present invention has achieved the following beneficial effects:
[0025] During the charging process of the negative electrode plate of the lithium-ion battery provided by the present invention, the hard carbon layer far away from the negative electrode current collector can quickly receive lithium ions in the electrolyte, avoiding the lithium precipitation phenomenon caused by the accumulation of lithium ions on the electrode surface during high-rate current charging. At the same time, the high-porosity hard carbon can play a certain buffering effect after quickly receiving a large number of lithium ions, and then transfer the lithium ions to the graphite layer, and the graphite layer ensures that the battery has a high energy density. The present invention improves the fast charging performance of lithium-ion batteries while maintaining a high energy density through the appropriate composite layer structure, surface density, compaction density and particle size design of graphite particles and hard carbon particles; and the negative electrode plate also has good flexibility, which alleviates the problems of breakage and powder loss during the processing process. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The drawings constituting part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute an improper limitation of the present invention. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0027] Figure 1 is a schematic structural diagram of a lithium-ion negative electrode sheet in a specific embodiment of the present invention;
[0028] Figure 2 is a scanning electron microscope image of a cross section of a lithium-ion negative electrode sheet of Example 1 of the present invention;
[0029] In the figure, S1, negative electrode current collector; S2, graphite layer; S3, hard carbon layer. DETAILED DESCRIPTION
[0030] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0031] The present invention provides a lithium ion battery negative electrode plate, comprising:
[0032] Anode current collector;
[0033] A graphite layer is disposed on both sides of the negative electrode current collector; the graphite layer comprises graphite particles, a conductive agent and a binder;
[0034] A hard carbon layer is arranged on the surface of the graphite layer away from the negative electrode current collector; the hard carbon layer comprises hard carbon particles, a conductive agent and a binder;
[0035] Wherein, the graphite layer and the hard carbon layer satisfy the relationship shown in Formula I:
[0036] 1.4≤ρ1*D1+ρ2*D2+PD≤1.75 Formula I;
[0037] Where ρ1 is the surface density of the hard carbon layer in g / cm 2 D1 is the D50 value of the hard carbon particles in the hard carbon layer when the unit is μm; ρ2 is the surface density of the graphite layer in g / cm 2 D2 is the surface density value of the graphite layer when D50 is in μm; PD is the compacted density in g / cm 3 The overall compacted density value at .
[0038] In some specific embodiments of the present invention, the graphite layer and the hard carbon layer are disposed on both sides of the negative electrode current collector, see Figure 1 , Figure 1 This is a schematic diagram of the structure of the negative electrode plate provided by the present invention (double-layer coating). Figure 1 In the figure, S1: negative electrode current collector; S2: graphite layer; S3: hard carbon layer. Accordingly, with S1 as the symmetry axis, the double-layer coated graphite layer and hard carbon layer are symmetrically arranged, that is, a structure of hard carbon layer / graphite layer / negative electrode current collector / graphite layer / hard carbon layer is formed.
[0039] The negative electrode plate of the present invention includes a graphite layer close to the negative electrode current collector and a hard carbon layer away from the negative electrode current collector. The design is to make the hard carbon layer contact the electrolyte first. The hard carbon layer has good adsorption performance and can receive lithium ions in the electrolyte in time, avoiding the lithium ion transmission speed in the electrolyte when charging at a high rate too fast and the lithium precipitation problem caused by the aggregation on the negative electrode surface. Then, the hard carbon layer with high porosity has good lithium insertion performance, which can receive a large amount of lithium ions, forming a certain buffer, and then the lithium ions are transferred to the graphite layer, ensuring that the battery has good fast charging performance. The graphite layer has a high energy density, which can ensure that the battery has a high energy density. The surface density, compaction density and particle size of the hard carbon layer and the graphite layer will affect the direct current internal resistance (DCR) of the battery. The present invention summarizes formula I as the design standard of the graphite layer and the hard carbon layer through a large number of experiments. The battery assembled by the negative electrode plate meeting formula I can maintain a high energy density while having a high fast charging performance.
[0040] In the present invention, the mass ratio of the graphite layer to the hard carbon layer is (40:60) to (60:40). The mass ratio of the two will affect the fast charging performance and energy density of the battery.
[0041] In the present invention, the graphite layer and the hard carbon layer satisfy the relationship shown in Formula II:
[0042] 1.5≤ρ1*D1+ρ2*D2+PD≤1.72Formula II.
[0043] In the present invention, ρ1 is 0.0048-0.012; D1 is 3-18; ρ2 is 0.0048-0.012; D2 is 8-20; PD is 1.3-1.6. Further, ρ1 is 0.006-0.01; D1 is 5-10; ρ2 is 0.006-0.01; D2 is 10-18; PD is 1.35-1.55; this range can ensure that formula I is satisfied, so that the negative electrode plate has better fast charging performance and energy density.
[0044] The mass ratio of graphite particles, conductive agent and binder in the graphite layer of the present invention is (90-95): (2-5): (2-5), and the mass ratio of hard carbon particles, conductive agent and binder is (90-95): (2-5): (2-5). The present invention does not impose any special restrictions on the types of conductive agents and binders in the graphite layer and the hard carbon layer, and the types of conductive agents and binders commonly used in the art can be used. For example, the binder can be selected from one or more of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), polyethylene acrylic acid (PEAA), polyvinyl alcohol (PVA), polyacrylonitrile (PAN), sodium hydroxymethyl cellulose (CMC), sodium alginate, polyvinylidene fluoride (PVDF), etc.; the conductive agent is preferably one or more of carbon black, conductive graphite, carbon nanotubes, nano-carbon fibers, graphene, etc.
[0045] In the present invention, the total mass per unit area of the graphite layer and the hard carbon layer on one side of the negative electrode current collector is 6 to 10 mg / cm 2 The total mass per unit area specifically refers to the unit area (1cm 2 ) on the graphite layer and the total mass of the hard carbon layer.
[0046] The present invention provides a method for preparing the above-mentioned negative electrode sheet of a lithium ion battery, comprising the following steps:
[0047] Graphite particles, conductive agent and binder are mixed evenly with solvent to form a first slurry, hard carbon particles, conductive agent and binder are mixed evenly with solvent to form a second slurry, and the first slurry and the second slurry are coated on one side of the negative electrode collector by double-layer coating equipment, and the first slurry is in contact with the surface of the negative electrode collector; after drying, the first slurry and the second slurry are coated on the other side of the negative electrode collector in the same way, and the first slurry is in contact with the surface of the negative electrode collector, and the negative electrode sheet of the lithium-ion battery is obtained after drying.
[0048] The present invention does not impose any special restrictions on the selection of solvents, and those skilled in the art can determine the selection of solvents according to the type of the selected binder. The present invention does not impose any special restrictions on the preparation process of the first slurry and the second slurry, and the commonly used methods in the art can be used.
[0049] The present invention provides a lithium ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. The negative electrode sheet is the above-mentioned lithium ion battery negative electrode sheet or the lithium ion battery negative electrode sheet prepared by the above-mentioned preparation method.
[0050] The present invention does not impose any special restrictions on the positive electrode plate, separator and electrolyte, and the positive electrode plate, separator and electrolyte commonly used in the art can be used; the present invention does not impose any special restrictions on the manufacturing method of the above-mentioned lithium-ion battery, and the manufacturing method of the lithium-ion battery commonly used in the art can be used.
[0051] The technical solution of the present invention is further described below in conjunction with specific embodiments. In the following embodiments, D50 refers to the particle size corresponding to when the cumulative particle size distribution percentage reaches 50%.
[0052] Example 1
[0053] This embodiment provides a method for preparing a negative electrode plate of a lithium-ion battery. The D50 of the hard carbon powder in this embodiment is 9 μm, and the D50 of the artificial graphite particles is 15 μm.
[0054] Artificial graphite, conductive carbon black, CMC and SBR are mixed in a mass ratio of 94:1:2:3, and then deionized water is added in a high-speed mixer and evenly mixed into a first slurry with a solid content of 48%. Hard carbon powder, conductive carbon black, carbon nanotubes, CMC and SBR are mixed in a mass ratio of 94:1:2:3, and then deionized water is added in a high-speed mixer and evenly mixed into a second slurry with a solid content of 48%. The two slurries are coated on a single side of a copper foil with a thickness of 8 microns using a double-layer coating device, with the first slurry in the lower layer and the second slurry in the upper layer, at a weight ratio of 40:60, and dried to keep the weight of the coating per unit area after drying at 8.5 mg / cm 2 Then, the same process is used to coat and dry the other side of the copper foil to obtain the negative electrode semi-finished product. 3 Rolling is performed to obtain a rolled negative electrode sheet, and finally a negative electrode sheet structure of hard carbon layer / graphite layer / negative electrode current collector / graphite layer / hard carbon layer is obtained.
[0055] The cross-sectional scanning electron microscope image of the negative electrode sheet of Example 1 is as follows: Figure 2 As shown in the figure, it can be seen that the particles in the upper layer (the layer far away from the copper foil) are smaller, and the particles in the lower layer (the layer close to the copper foil) are larger. The smaller particles in the upper layer give it a larger specific surface area, so that it can receive lithium ions in the electrolyte faster, which is conducive to improving the fast charging performance.
[0056] Example 2
[0057] This embodiment provides a method for preparing a negative electrode plate of a lithium-ion battery. The D50 of the hard carbon powder in this embodiment is 9 μm, and the D50 of the artificial graphite particles is 15 μm.
[0058] Artificial graphite, conductive carbon black, CMC and SBR are mixed in a mass ratio of 94:1:2:3, and then deionized water is added in a high-speed mixer and evenly mixed into a first slurry with a solid content of 48%. Hard carbon powder, conductive carbon black, carbon nanotubes, CMC and SBR are mixed in a mass ratio of 94:1:2:3, and then deionized water is added in a high-speed mixer and evenly mixed into a second slurry with a solid content of 48%. The two slurries are coated on a single side of a copper foil with a thickness of 8 microns using a double-layer coating device, with the first slurry in the lower layer and the second slurry in the upper layer, at a weight ratio of 50:50, and dried to keep the weight of the coating per unit area after drying at 8.5 mg / cm 2 Then, the same process is used to coat and dry the other side of the copper foil to obtain the negative electrode semi-finished product. 3 Roll-pressing is performed to obtain a rolled negative electrode sheet.
[0059] Example 3
[0060] This embodiment provides a method for preparing a negative electrode plate of a lithium-ion battery. The D50 of the hard carbon powder in this embodiment is 9 μm, and the D50 of the artificial graphite particles is 15 μm.
[0061] Artificial graphite, conductive carbon black, CMC and SBR are mixed in a mass ratio of 94:1:2:3, and then deionized water is added in a high-speed mixer and evenly mixed into a first slurry with a solid content of 48%. Hard carbon powder, conductive carbon black, CMC and SBR are mixed in a mass ratio of 94:1:2:3, and then deionized water is added in a high-speed mixer and evenly mixed into a second slurry with a solid content of 48%. The two slurries are coated on a single side of a copper foil with a thickness of 8 microns using a double-layer coating device, with the first slurry in the lower layer and the second slurry in the upper layer, at a weight ratio of 60:40, and dried to keep the weight of the coating per unit area after drying at 8.5 mg / cm 2 Then, the same process is used to coat and dry the other side of the copper foil to obtain the negative electrode semi-finished product. 3 Roll-pressing is performed to obtain a rolled negative electrode sheet.
[0062] The differences between Examples 4 to 6 and Comparative Examples 1 to 3 and Example 2 are listed in Table 1. The other preparation methods remain the same. Comparative Example 4 only has a graphite layer and does not contain a hard carbon layer; Comparative Example 5 only has a hard carbon layer and does not contain a graphite layer.
[0063] Test example
[0064] 1. Preparation of positive electrode sheet: Mix the positive electrode active material powder (lithium iron phosphate), conductive carbon black, carbon nanotubes and PVDF in a mass ratio of 94:2:1:3, then add N-methylpyrrolidone (NMP) in a high-speed mixer and mix evenly into a positive electrode slurry with a solid content of 60wt%. The positive electrode slurry is coated on one side of a 12μm thick aluminum foil using a transfer coater and dried to maintain a unit area coating weight of 17.5mg / cm after drying. 2 Then, the same process is used to coat and dry the other side of the aluminum foil to obtain the positive electrode semi-finished product. 3 Roll-pressing is performed to obtain a rolled positive electrode sheet.
[0065] 2. Preparation of lithium-ion battery: The exposed metal foil of the above-mentioned positive electrode sheet and the negative electrode sheet of the embodiment and the comparative example is processed and welded into a pole ear, and then wound with a separator (PE separator) to form a winding core. The winding core is wrapped with an aluminum-plastic film to form a semi-finished battery cell, and then the electrolyte is injected, and the finished lithium-ion battery is obtained through the formation and capacity separation steps.
[0066] 3. Battery performance test:
[0067] (1) Dynamic performance test
[0068] At 25°C, the batteries prepared in the examples and comparative examples were fully charged at x C and fully discharged at 1 C for 10 times, and then the batteries were fully charged at x C again, and then the negative electrode plates were disassembled and the lithium deposition on the surface of the negative electrode plates was observed. If no lithium deposition was observed on the negative electrode surface, the charging rate x C was increased by 0.1 C as a gradient and tested again until lithium deposition was observed on the negative electrode surface, and the test was stopped. The charging rate (x-0.1) C at this time was the maximum charging rate of the battery.
[0069] (2) Energy density test
[0070] At 25°C, the lithium-ion battery prepared in the embodiment and the comparative example is fully charged at a 1C rate and fully discharged at a 1C rate, and the actual discharge energy at this time is recorded; at 25°C, the lithium-ion battery is weighed using an electronic balance; the ratio of the actual discharge energy of the lithium-ion battery at 1C to the weight of the lithium-ion battery is the actual energy density of the lithium-ion battery. Among them, when the actual energy density is less than 80% of the expected energy density, the actual energy density of the battery is considered to be very low; when the actual energy density is greater than or equal to 80% of the expected energy density and less than 95% of the expected energy density, the actual energy density of the battery is considered to be low; when the actual energy density is greater than or equal to 95% of the expected energy density and less than 105% of the expected energy density, the actual energy density of the battery is considered to be moderate; when the actual energy density is greater than or equal to 105% of the expected energy density and less than 120% of the expected energy density, the actual energy density of the battery is considered to be high; when the actual energy density is more than 120% of the expected energy density, the actual energy density of the battery is considered to be very high.
[0071] The test results are shown in Table 1.
[0072] Table 1 Experimental parameters and performance measurements of the embodiments and comparative examples
[0073]
[0074]
[0075] In Table 1, the calculated value is ρ1*D1+ρ2*D2+PD, where ρ1 is the surface density of the hard carbon layer in g / cm 2 D1 is the D50 value of the hard carbon particles in the hard carbon layer when the unit is μm; ρ2 is the surface density of the graphite layer in g / cm 2 D2 is the surface density value of the graphite layer when D50 is in μm; PD is the compacted density in g / cm 3 The compacted density value at .
[0076] As can be seen from Table 1, the lithium-ion battery made from the negative electrode sheet of the embodiment exhibits moderate energy density and high charging rate, which can meet the demand for high-rate charging, and all meet 1.4≤ρ1*D1+ρ2*D2+PD≤1.75. Double-layer coated negative electrode sheets that are not within this range are difficult to simultaneously obtain moderate energy density and high charging rate. The negative electrode sheet containing only a graphite layer has a high energy density but a low charging rate; the negative electrode sheet containing only a hard carbon layer has a high charging rate but a low energy density.
[0077] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A negative electrode plate for a lithium-ion battery, characterized in that: include: Anode current collector; A graphite layer is disposed on both sides of the negative electrode current collector; the graphite layer comprises graphite particles, a conductive agent and a binder; A hard carbon layer is arranged on the surface of the graphite layer away from the negative electrode current collector; the hard carbon layer comprises hard carbon particles, a conductive agent and a binder; Wherein, the graphite layer and the hard carbon layer satisfy the relationship shown in Formula I: 1.4≤ρ1*D1+ρ2*D2+PD≤1.75Formula I; Where ρ1 is the surface density of the hard carbon layer in g / cm 2 D1 is the D50 value of the hard carbon particles in the hard carbon layer when the unit is μm; ρ2 is the surface density of the graphite layer in g / cm 2 D2 is the surface density value of the graphite layer when D50 is in μm; PD is the compacted density in g / cm 3 The overall compacted density value at .
2. The negative electrode plate of a lithium-ion battery according to claim 1, characterized in that: The mass ratio of the graphite layer to the hard carbon layer is (40:60) to (60:40).
3. The negative electrode plate of a lithium-ion battery according to claim 1, characterized in that: The graphite layer and the hard carbon layer satisfy the relationship shown in Formula II: 1.5≤ρ1*D1+ρ2*D2+PD≤1.72Formula II.
4. The negative electrode plate of a lithium-ion battery according to claim 3, characterized in that: ρ1 is 0.0048~0.012; D1 is 3~18; ρ2 is 0.0048~0.012; D2 is 8~20; PD is 1.3~1.
6.
5. The negative electrode plate of a lithium-ion battery according to claim 4, characterized in that: ρ1 is 0.006~0.01; D1 is 5~10; ρ2 is 0.006~0.01; D2 is 10~18; PD is 1.35~1.
55.
6. The negative electrode plate of a lithium-ion battery according to claim 1, characterized in that: In the graphite layer, the mass ratio of graphite particles, conductive agent and binder is (90-95):(2-5):(2-5).
7. The negative electrode plate of a lithium-ion battery according to claim 1, characterized in that: In the hard carbon layer, the mass ratio of the hard carbon particles, the conductive agent and the binder is (90-95):(2-5):(2-5).
8. The negative electrode plate of a lithium-ion battery according to claim 1, characterized in that: The total mass per unit area of the graphite layer and the hard carbon layer on one side of the negative electrode current collector is 6 to 10 mg / cm 2 .
9. The method for preparing a negative electrode sheet for a lithium ion battery according to any one of claims 1 to 8, characterized in that: The steps include: Graphite particles, conductive agent and binder are mixed evenly with solvent to form a first slurry, hard carbon particles, conductive agent and binder are mixed evenly with solvent to form a second slurry, and the first slurry and the second slurry are coated on one side of the negative electrode collector by double-layer coating equipment, and the first slurry is in contact with the surface of the negative electrode collector; after drying, the first slurry and the second slurry are coated on the other side of the negative electrode collector in the same way, and the first slurry is in contact with the surface of the negative electrode collector, and the negative electrode sheet of the lithium-ion battery is obtained after drying.
10. A lithium ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, characterized in that: The negative electrode plate is the negative electrode plate of a lithium ion battery according to any one of claims 1 to 8 or the negative electrode plate of a lithium ion battery prepared by the preparation method according to claim 9.
Citation Information
Patent Citations
Lithium ion battery negative electrode piece using hard carbon and soft carbon as active materials and lithium ion battery
CN103633293A
Negative pole piece of lithium ion battery
CN119008854A
Cited By
Gradient-coated graphite composite negative electrode material, preparation method thereof and lithium ion battery
CN120565651A
Secondary battery
CN120657055A
A secondary battery
CN120657055B